Antibiotics Affect ROS Production and Fibroblast Migration in an In-vitro Model of Sinonasal Wound Healing - Gouzos, Michael; Ramezanpour, Mahnaz; Bassiouni, Ahmed; Psaltis, Alkis J.; Wormald, P. J.; Vreugde, Sarah (Frontiers in Cellular and Infection Microbiology, 2020)
Introduction: Antibiotics are often administered to patients perioperatively and have been shown to affect ROS production of nasal cells in vitro, but their effect in the setting of active wound healing remains unclear. Reactive oxygen species (ROS) are known to play a significant role in wound healing. This study analyzed a broad array of antibiotics used after sinus surgery to assess their effect on wound healing and ROS production in vitro. It was hypothesized that ROS production would be affected by these antibiotics and there would be a negative relationship between ROS activity and cell migration speed. Methods: Monolayers of primary human nasal epithelial cells (HNEC) and primary fibroblasts were disrupted with a linear wound, treated with 10 different antibiotics or a ROS inhibitor and observed over 36 hours in a controlled environment using confocal microscopy. ROS activity and migration speed of the wound edge were measured at regular intervals. The relationship between the two parameters was analyzed using mixed linear modelling. Results: Performing a linear scratch over the cell monolayers produced an immediate increase in ROS production of approximately 35% compared to unscratched controls in both cell types. Incubation with mitoquinone and the oxazolidinone antibiotic linezolid inhibited ROS activity in both fibroblasts and HNEC in association with slowed fibroblast cell migration (p<0.05). Fibroblast cell migration was also reduced in the presence of clarithromycin and mupirocin (p<0.05). A significant correlation was seen between ROS suppression and cell migration rate in fibroblasts for mitoquinone and all antibiotics except for azithromycin and doxycycline, where no clear relationship was seen. Treatments that slowed fibroblast cell migration compared to untreated controls showed a significant correlation with ROS suppression (p<0.05). Conclusion: Increased ROS production in freshly wounded HNEC and fibroblast cell monolayers was suppressed in the presence of antibiotics, in correlation with reduced fibroblast cell migration. In contrast, HNEC cell migration was not significantly affected by any of the antibiotics tested. This differential effect of antibiotics on fibroblast and HNEC migration might have clinical relevance by reducing adhesion formation without affecting epithelial healing in the postoperative setting.